A perfused multi-well bioreactor platform to assess tumor organoid response to a chemotherapeutic gradient - Wasson, Elisa Marie; He, Wei; Ahlquist, Jesse; Hynes, William Fredrick; Triplett, Michael Gregory; Hinckley, Aubree; Karelehto, Eveliina; Gray-Sherr, Delaney Ruth; Friedman, Caleb Fisher; Robertson, Claire; Shusteff, Maxim; Warren, Robert; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
There is an urgent need to develop new therapies for colorectal cancer that has metastasized to the liver and, more fundamentally, to develop improved preclinical platforms of colorectal cancer liver metastases (CRCLM) to screen therapies for efficacy. To this end, we developed a multi-well perfusable bioreactor capable of monitoring CRCLM patient-derived organoid response to a chemotherapeutic gradient. CRCLM patient-derived organoids were cultured in the multi-well bioreactor for seven days and the subsequently established gradient in 5-fluorouracil (5-FU) concentration resulted in a lower IC50 in the region near the perfusion channel versus the region far from the channel. We compared behaviour of organoids in this platform to two commonly used PDO culture models: organoids in media and organoids in a static (no perfusion) hydrogel. The bioreactor IC50 values were significantly higher than IC50 values for organoids cultured in media whereas only the IC50 for organoids far from the channel were significantly different than organoids cultured in the static hydrogel condition. Using finite element simulations, we showed that the total dose delivered, calculated using area under the curve (AUC) was similar between platforms, however normalized viability was lower for the organoid in media condition than in the static gel and bioreactor. Our results highlight the utility of our multi-well bioreactor for studying organoid response to chemical gradients and demonstrate that comparing drug response across these different platforms is nontrivial.